Needs Analysis: Social Skills-Based Learning Model For Children With Learning Disabilities at an Inclusive School - Husadani, Rizki; Suryani, Nunuk; Yusuf, Munawir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to explore the needs of social skills-based learning models for inclusive schools for children with learning disabilities. The research method used was a quantitative descriptive approach. The research subjects were teachers who teach children with learning disabilities in eight inclusive elementary schools in Surakarta. The technique to get the data collection used was aÂ structured questionnaire with Likert scale. Then, it was analyzed using descriptive statistical analysis techniques by categorizing i.e. The analysis results showed that the level of needs of a social skills-based learning model for children with learning disabilities was very high with final percentage of 83%. Therefore, it was necessary to develop a skill-based learning model for children with learning disabilities in an inclusive school to assist teachers in developing social skills for children with learning disabilities.